What Becomes of the Avant-Guarded? New Music as Subculture - Iddon, Martin (Circuit, 2014)
In a short ‘vox pop,’ written for Circuit in 2010, on the subject of the ‘future’ of new music, I proposed that new music — or the version of it tightly intertwined with what was once thought of as the international avant-garde, at any rate — might today be better thought of as a sort of subculture, akin to the spectacular subcultures of goth and punk, but radically different in that they developed from the ‘grassroots,’ as it were, while new music comes from a position of extreme cultural privilege, which is to say it has access, even now, to modes of funding and infrastructure subcultures ‘proper’ never have. This essay develops this line of enquiry, outlining theories of subculture and post-subculture — drawing on ‘classic’ and more recent research, from Hebdige and Cohen to Hodkinson, Maffesoli, and Thornton — before presenting the, here more detailed, case that new music represents a sort of subculture, before making some tentative proposals regarding what sort of subculture it is and what this might mean for contemporary understandings of new music and what it is for.